2022
DOI: 10.1007/s40195-022-01473-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of V Addition on Microstructural Evolution and Mechanical Properties of AlCrFe2Ni2 High-Entropy Alloys

Abstract: The effects of vanadium addition on the microstructural evolution and mechanical properties of AlCrFe 2 Ni 2 high-entropy alloy (HEA) were investigated. The results showed that the AlCrFe 2 Ni 2 V 0.2 HEA was composed of FCC phase, disordered BCC phase, and ordered BCC (B2) phase. With the increase in vanadium content, the formation of FCC phase was inhibited, and a transition from FCC phase to BCC phase occurred. The FCC phase disappeared completely when the value of x exceeds 0.4 in AlCrFe 2 Ni 2 V x HEAs. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Chen et.al, [20] discovered that increasing the V content boosted the hardness and wear resistance properties of the Al0.5CoCrCuFeNi HEA. In AlCrFe2Ni2Vx HEAs, Duan et.al, [21] found that an increase in V content prevented the development of the FCC phase and caused a change from the FCC phase to the BCC phase. The yield strength of AlCrFe2Ni2Vx alloys rose with increasing V content, which was mostly caused by the lowering concentration of FCC phase and the strengthening of V element in solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et.al, [20] discovered that increasing the V content boosted the hardness and wear resistance properties of the Al0.5CoCrCuFeNi HEA. In AlCrFe2Ni2Vx HEAs, Duan et.al, [21] found that an increase in V content prevented the development of the FCC phase and caused a change from the FCC phase to the BCC phase. The yield strength of AlCrFe2Ni2Vx alloys rose with increasing V content, which was mostly caused by the lowering concentration of FCC phase and the strengthening of V element in solid solution.…”
Section: Introductionmentioning
confidence: 99%